Contoh Artikel - Fikri Maulanda; Eka Purwa Laksana; Indra Riyanto (MAESTRO, 2023)
A flood is a natural disaster that occurs due to high rainfall and causes the overflow of rivers or streams that cause many losses to humans and can be an impact that causes electrical short circuits. This can certainly lead to harm such as injury, injury, even loss of life. In certain areas, many are still affected by flooding, especially in Jakarta and its surroundings. Many measures taken to deal with flooding have not been sufficiently effective, but few have cared for their own safety in the face of the effects of flooding. In this final assignment he designed a prototype model of an automatic power cutting system for flood disaster response homes. Designed on a 1:10 scale system with a height of actually 200 cm. Prototype models are made for simulation testing to facilitate the system in testing. The system consists of an ultrasonic sensor, an MCB, a servo, a traffic light indicator in the form of a light, a buzzer in the form of a sound, and an LCD 16x2 as a display of the sensor readings. The process in the system with the reading of the distance of the water surface uses the HC-SR04 ultrasonic sensor to produce a high value of water with the calculations on the program. And the calculation for the accuracy of the ultrasonic sensor readings uses the RMSE (root mean square error) formula and gets an RMSE value of 0.20 - 0.95 Cm where 0.20 Cm is the lowest RMSE value at 15 Cm water height and 0.95 Cm is the highest RMSE value at 10 Cm water height. The working principle of the system is to read the distance of the water surface to produce a high value of water, the high value of water is divided into 3 statuses, namely safe at a height of 0-7 Cm, alert at a height of 8-14 Cm, and flooding at a height of 15 Cm. At a height of 15 Cm and declare the flood status results that cause automatic power breaks.. Keywords : Fresidential flood, ultrasonic sensors, prototype model